Evolution of concomitant moderate and moderate to severe functional mitral regurgitation following aortic valve surgery for severe aortic stenosis - Dabić, Petar; Borović, Saša; Milojević, Predrag; Kostić, Jelena V; Trifunović, Zoran; Babić, Rade (Vojnosanitetski pregled, 2021)
Background/Aim. Functional mitral regurgitation (FMR) is a common entity in patients with aortic stenosis (AS) undergoing aortic valve replacement (AVR). The aim of this study was to examine evolution of moderate and moderate to severe FMR after an isolated AVR, to identify prognostic indicators for persistent MR postoperatively, and to offer the recommendation regarding surgical intervention for moderate and moderate to severe FMR at the time of AVR for AS. Methods. We retrospectively reviewed 39 consecutive patients with moderate and moderate to severe FMR at the time of isolated AVR from January 2007 to December 2013. We collected preoperative and postoperative echocardiographic data to determine the evolution of FMR after AVR. Patients were divided into the persistent (n = 14) and improved FMR group (n = 25). Secondary division was into the prosthesis-patient mismatch (PPM, n = 7) and non prosthesis-patient mismatch group (non PPM, n = 32 patients). Late follow-up echocardiography was completed in 100% (39/39) of patients. Results. FMR improved postoperatively (MR ˂ 2+) in 64% (25/39) of patients, while 36% (14/39) of patients had persistent MR ≥ 2). In comparison to the persistent group, the patient with improved FMR had significant decrease in the left ventricular end-diastolic diameter, left ventricular end-systolic diameter, posterior wall and septum thickness postoperatively. The same indicators of reverse remodeling were found in the non PPM group in comparison to the PPM group. The incidence of postoperative FMR improvement was higher in the non PPM group (65.6%, p = 0.001) in comparison to thePPM group (42.9%, p = 0.125). The mean follow-up duration was 39.5 ± 23.5 months. Conclusion. In accordance with previous studies, this study also showed improvement in FMR following AVR surgery. Improvement in MR degree was associated with echocardiographic parameters of reverse left ventricular remodeling. Conservative approach is advisable in patients with moderate and moderate to severe FMR, believing that repair or replacement is unnecessary at the time of AVR for severe AS. PPM could prevent downgrading of FMR, stressing out the importance of choosing the prosthesis of adequate size.